Essentials of negotiation / Roy J Lewicki; Bruce Barry; David M Saunders - Lewicki, Roy J.
"The objective of this shorter version is to provide the reader with the core concepts of negotiation in a more succinct presentation. Many faculty requested such a book for use in shorter academic course, executive education programs, or as a companion to other resource materials. It is suitable for courses in negotiation, labor relations, conflict management, human resource management, and the like"